Implementation of the Requirements for Church Overseers Based on 1 Timothy 3:1-7 Among the Church Management of GKII Sintang - Athanasius, Yesias; Purwoko, Paulus Sentot; Wahyuni, Sri (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
The purpose of this research is to find out how big the level of implementation of the Apostle Paul's Teaching on the Conditions of Congregational Overseers based on 1 Timothy 3:1-7 Among the Congregational Management of the Indonesian Gospel Tent Church Sintang I Region II West Kalimantan. This research uses quantitative descriptive research. Called quantitative because the data obtained based on the number of objects or respondents studied, can be calculated according to a predetermined formula. Collecting data using a Likert scale and processing it through several tests using SPSS 25. The tests used are instrument validation and reliability tests as well as normality tests, homogeneity tests and hypothesis tests. To test the hypothesis using the Convidence Interval formula at a significance level of 5%, regression significance test (Freg) and one way variance test (one way Anova) also using data collection techniques through the literature, namely the Bible in various versions, Bible dictionaries, interpretations -interpretations, Bible Encyclopedias, Interlinears, and various online and offline reading sources. The results show that the Implementation of the Apostle Paul's Teaching Regarding the Conditions of Congregational Overseers Based on 1 Timothy 3:1-7 Among the Congregational Management of the Indonesian Evangelical Camp Church in Sintang I Region II West Kalimantan (Y) is in the medium category, this is not in accordance with the proposed hypothesis. . The proposed hypothesis is low.